Clinical Efficacy and Safety of Propranolol in the Prevention and Treatment of Retinopathy of Prematurity: A Meta-Analysis of Randomized Controlled Trials - Kong, Haibo B.; Zheng, Guoyuan Y.; He, Baomei M.; Zhang, Ying; Zhou, Qin (Frontiers in Pediatrics, 2021)
Objective: To perform a meta-analysis of randomized controlled trials verifying clinical efficacy and safety of propranolol in preterm newborns with ROP. Methods: We searched the literature databases (Pubmed, Embase, The Cochrane Library, Web of Science, CNKI, WanFang, VIP, CBM) for publications before August 10, 2020, and the World Health Organization’s International Clinical Trials Registry and ClinicalTrials.gov for ongoing trials. Randomized controlled trials (RCTs) of propranolol for the prevention or treatment of ROP were included. The quality of the included studies was primarily assessed by the Randomized Controlled Trial tool of the Cochrane Collaboration. The included studies were quantified using a meta-analysis relative risk (RR) estimated with a random effect model. Results: Our original search identified 171 articles, and five studies met our criteria. A meta-analysis was performed which showed that infants orally treated with propranolol had a decreased risk of disease progression: stage progression had an RR = 0.65 [95% confidence interval (CI), 0.47 to 0.88]), and plus disease had an RR = 0.43 [95% CI, 0.22 to 0.82]. The demands for additional treatments had similar protective results: laser photocoagulations had an RR = 0.55 [95% CI, 0.35 to 0.86]), and intravitreal injection of anti-VEGF had an RR = 0.45 [95% CI, 0.22 to 0.90]). The oral administration of propranolol was associated with an increased risk of adverse events (RR=2.01 [95% CI, 1.02 to 3.97]). High-risk adverse events included bradycardia, hypotension, not getting enough weight, bronchospasm, hypoglycemia, apnea and increasing ventilator need. Subgroup analysis of ROP phases and stages found that the risk in Stage 2 ROP of second phase, and the individual risk factors (stage progression, RR = 0.42 [95% CI, 0.27 to 0.65]; plus disease, RR = 0.40 [95% CI, 0.17 to 0.93]; laser photocoagulation, RR = 0.31 [95% CI, 0.14 to 0.68]) have statistically significant differences compared with other phases and stages. Conclusions: Preterm newborns with ROP, especially in Stage 2 ROP of second phase, who were orally given propranolol, have a reduced risk of disease progression and the demands for additional treatments, but the safety needs more attention.